2-(4-Nitrophenyl)isothiazol-3(2H)-one: A Promising Selective Agent against Hepatocellular Carcinoma Cells - Sofia Marka; Maria-Eleftheria Zografaki; Georgia Tsolomiti; Katerina I. Kalliampakou; Athanasios Tsolomitis; Christina Koumantou; Despina Smirlis; Niki Vassilaki; Spyros Kintzios (MDPI AG, 2024)
Liver cancer ranks among the most prevalent malignancies globally and stands as a leading cause of cancer-related mortality. Numerous isothiazolone derivatives and analogues have been synthesized and investigated for their potential as anticancer agents; however, limited data exist regarding their efficacy against liver cancer. In the present study, two nitrophenyl-isothiazolones, the 5-benzoyl-2-(4-nitrophenyl)isothiazol-3(2H)-one (IsoA) and the 2-(4-nitrophenyl)isothiazol-3(2H)-one (IsoB), were preliminarily investigated for their cytotoxicity against hepatoma human (Huh7) cells as a liver cancer model and Immortalized Human Hepatocytes (IHHs) as a model of non-cancerous hepatocytes. IsoB, derived from IsoA after removal of the benzoyl moiety, demonstrated the highest cytotoxic effect against Huh7 cells with CC50 values of 19.3 μΜ at 24 h, 16.4 μΜ at 48 h, and 16.2 μΜ at 72 h of incubation, respectively. IsoB also exhibited selective toxicity against the liver cancerous Huh7 cells compared to IHH cells, reinforcing its role as a potent and selective anticancer agent. Remarkably, the cytotoxicity of IsoB was higher when compared with the standard chemotherapeutical agent 5-fluorouracil (5-FU), which also failed to exhibit higher toxicity against the liver cancerous cell lines. Moreover, IsoB-treated Huh7 cells presented a noteworthy reduction in mitochondrial membrane potential (ΔΨm) after 48 and 72 h, while mitochondrial superoxide levels showed an increase after 24 h of incubation. The molecular mechanism of the IsoB cytotoxic effect was also investigated using RT-qPCR, revealing an apoptosis-mediated cell death along with tumor suppressor TP53 overexpression and key-oncogene MYCN downregulation.